2015
DOI: 10.1177/1066480714565106
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the Marriage Relationship During the Doctoral Journey

Abstract: With doctoral programs across disciplines experiencing perennially high attrition rates, in-depth examination of factors associated with doctoral persistence is necessary. A strong marital relationship is one factor found to be central to persistence in doctoral students. Thus, the purpose of this article is to provide an overview of the literature on marital satisfaction, quality, and stability in order to provide doctoral students and their partners strategies for nurturing and sustaining a solid marriage th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
3
0
3
Order By: Relevance
“…Family value of the degree, family support, family adaption, and clearly negotiated roles were also essential to development and persistence. While some women in this study had spouses willing to take on more non-traditional or supportive roles, other women reported that their negotiated roles and division of labor remained mostly traditional, a finding consistent with prior research (Lyonette et al, 2015;Rockinson-Szapkiw, Spaulding, & Knight, 2015). The theme of motherhood and family as a motivation to develop and persist was not surprising given the fact that all participants were mothers and described motherhood as significant.…”
Section: Discussionsupporting
confidence: 84%
“…Family value of the degree, family support, family adaption, and clearly negotiated roles were also essential to development and persistence. While some women in this study had spouses willing to take on more non-traditional or supportive roles, other women reported that their negotiated roles and division of labor remained mostly traditional, a finding consistent with prior research (Lyonette et al, 2015;Rockinson-Szapkiw, Spaulding, & Knight, 2015). The theme of motherhood and family as a motivation to develop and persist was not surprising given the fact that all participants were mothers and described motherhood as significant.…”
Section: Discussionsupporting
confidence: 84%
“…Internal conflict between the developing academic identity and other identities may result in denial or discontinuance of as-pects of self or relationships associated with specific identities (Eisenbach, 2013;Wellington & Sikes, 2006). Divorce and marital difficulties are documented consequences of the doctoral journey (Middleton, 2001;Norton, Thomas, Morgan, Tilley, & Dickins, 1998;Rockinson-Szapkiw, Spaulding, & Knight, 2015), and researchers have noted, "family and personal relationships are sometimes strained and can even break down as a result of a student's involvement in their studies" (Wellington & Sikes, 2006, p. 731). As the average age of a recipient of a doctoral degree is 33, which is around the age many women choose to begin a family (Mason, Wolfinger, & Golden, 2013), women may choose to delay beginning a family or choose not to have children.…”
Section: The Current State Of the Literature And The Gapmentioning
confidence: 99%
“…Se han identificado en la literatura, afectaciones emocionales y psicosociales propias del estudiante de doctorado. Estas incluyen el burnout (Löfström y Pyhältö, 2019), distrés y riesgo de desarrollo de un trastorno psiquiátrico (Levecque et al, 2017) y alteraciones en las relaciones interpersonales (Rockinson et al, 2015;Rockinson et al, 2017). Al ser parte del proyecto de vida y tener repercusiones psicosociales, los estudios doctorales son una vivencia que realiza el estudiante.…”
Section: Desarrollo Conceptualunclassified